Comparison of meloxicam, tamsulosin and combination of both drugs with 16 Fr and 20 Fr catheter on trial without catheter successfulness in patients with benign prostatic hyperplasia - Hasroni Fathurrahman; Doddy Moesbadianto Soebadi (Faculty of Medicine, Universitas Islam Indonesia, 2018)
Background: Acute urinary retention, is one of the main complications of Benign Prostatic Hyperplasia (BPH) in elderly patients. Trial Without Catheter (TWOC) is a way to evaluate whether a patient can urinate spontaneously after an episode of urinary retention. Objective: To prove that the combination of meloxicam 15 mg and tamsulosin 0.4 mg orally once daily for three weeks with 20 Fr catheter is more effective in the TWOC successfulness in BPH patients than meloxicam 15 mg or tamsulosin 0.4 mg alone with 16 Fr catheter. Methods: Patients BPH who had the first episode of urinary retention and fulfil the inclusion criteria were randomised. There were six treatment groups (n=6). The treatment group are meloxicam 15 mg + catheter 16 Fr (K1), combination of meloxicam 15 mg and tamsulosin 0.4 mg + catheter 16 Fr (K2), tamsulosin 0.4 mg + catheter 16 Fr (K3), meloxicam 15 mg + catheter 20 Fr (K4), combination of meloxicam 15 mg and tamsulosin 0.4 mg + catheter 20 Fr (K5), tamsulosin 0.4 mg + catheter 20 Fr (K6). For each group, drugs were given orally once daily for seven days. Efficacy of TWOC was assessed by the ability of spontaneous urinary after the first 24 hour post urethral catheter treatment, with Q-max result on uroflowmetry = 5 cc/sec and PVR = 100 cc. Result: All subjects from K1 and K4 experience a recurrent episode of urinary retention (100%), 83.3% in K3 and 66.7% in K6. In the combination group, K2 had 50% incidence of repeat urinary retention, while K5 had16.7%. From the whole group, a statistically significant difference with p <0.05 only can be found in K1 and K5 (p = 0.02).Conclusion: The combination of meloxicam 15 mg and tamsulosin 0.4 mg + 20 Fr catheter had a better effect in TWOC efficacy compared with the meloxicam 15 mg + catheter 16 Fr group.